Differential Effect of Anesthesia on Visual Cortex Neurons with Diverse Population Coupling. (15th March 2021) - Lee, Heonsoo; Tanabe, Sean; Wang, Shiyong; Hudetz, Anthony G.
Highlights: V1 neurons were classified based on firing rate, population coupling and spike width. The classified groups showed distinct spike patterns in response to flash stimuli. Anesthesia promoted strong association between population coupling and firing rate. Anesthesia suppressed the flash response, delayed and split its spike timing. Abstract: Cortical neurons display diverse firing patterns and synchronization properties. How anesthesia alters the firing response of different neuron groups relevant for sensory information processing is unclear. Here we investigated the graded effect of anesthesia on spontaneous and visual flash-induced spike activity of different neuron groups classified based on their spike waveform, firing rate, and population coupling (the extent neurons conform to population spikes). Single-unit activity was measured from multichannel extracellular recordings in deep layers of primary visual cortex of freely moving rats in wakefulness and at three concentrations of desflurane. Anesthesia generally decreased firing rate and increased population coupling and burstiness of neurons. Population coupling and firing rate became more correlated and the pairwise correlation between neurons became more predictable by their population coupling in anesthesia. During wakefulness, visual stimulation increased firing rate; this effect was the largest and the most prolonged in neurons that exhibited high population coupling and high firing rate. During anesthesia, the early increase in firing rate (20–150 ms post-stimulus) of these neurons was suppressed, their spike timing was delayed and split into two peaks. The late response (200–400 ms post-stimulus) of all neurons was also suppressed. We conclude that anesthesia alters the visual response of primarily high-firing highly coupled neurons, which may interfere with visual sensory processing. The increased association of population coupling and firing rate during anesthesia suggests a decrease in sensory information content.